Measuring polymerization shrinkage of composites utilizing a gas pycnometer - Cilli, Renato; Prakki, Anuradha; Araújo, Maria A. J. de (Brazilian Dental Science, 2010)
The objective of this laboratory study was to evaluate the volumetric contraction of five resin composites currently in use. A helium gas pycnometer was used to determine the volume of specimens prior to and after photopolymerization from which total volumetric contraction was obtained. The resin was weighed in an analytic balance and inserted into the pycnometer chamber, the volume of which is known, and hermetically sealed. The volume of the specimen was determined by measuring the pressure change of helium when it was opened up to the expansion chamber. In this study, 15 cycles of pressurizing were repeated for volume determination for each specimen. The arithmetic mean volume was obtained. The final volume was evaluated as done before. The percentage contraction (P) was calculated by: P = 100(SVi - SVf) / SVi, where SV is specific volume and the suffixes i and f indicate measurements before and after polymerization, respectively. The measured volumetric shrinkage ranged from 0.56% for Z250 (3M-ESPE) to 3.26% for P60 (3M-ESPE). The gas pycnometry is a promising method and its mechanism should be more explored for investigating dental materials.